BEYOND THE PLEASURE PRINCIPLE - FATAL CARDIAC ARRHYTHMIAS AFTER INGESTION OF AN HERBAL MEDICATION - Lakhdhir, Fahad; Alauddin, Umaira; Ul Haq, Ejaz; Qadir, Faisal (Journal of Ayub Medical College Abbottabad, 2022)
There is increasing popularity in the use of herbal medicine for different ailments as these natural products are considered safer than conventional medicines; however, their use in dosage exceeding prescribed limits can result in serious toxic side effects. We present a case of a 63-year-old male who presented with complaints of restlessness, nausea, vomiting and tingling sensation on his body and ECG evidence of bi-directional ventricular tachycardia. On interrogation, it was revealed that the patient had self-prepared and consumed large quantity of an herbal medication (containing toxic aconite roots) as therapy for erectile dysfunction resulting in a fatal outcome.